Student Self-Analysis of Their Nonsterile Preparations and its Effect on Compounding Confidence - Jih, Joyce S. (Am J Pharm Educ, 2018)
Objective. To determine if students who self-analyzed their own nonsterile preparations had increased confidence in their compounding skill. Methods. Self-efficacy surveys were given to P1 and P3 students at the beginning and conclusion of a semester in which they completed their regularly scheduled compounding course. The survey assessed their confidence in general compounding skills and their perception if an additional self-analytical component to determine the potency of their nonsterile preparations would improve their confidence level score. Results. P1 and P3 students reported increased confidence in all surveyed areas at the end of the semester, with P1 students showing more dramatic increases most likely due to this being their first compounding experience in this academic institution. P1 students reported a modest but significant decrease in their perception that potency self-analysis would affect their compounding ability [9.38 (SD 1.12) to 8.98 (SD 1.18)] while P3 students had a significant increase [8.09 (SD 2.18) to 8.68 (SD 1.82)] in the same item. This study also hypothesized that students who made nonsterile compounded preparations with <10% error would have greater confidence improvement. However, no statistical differences were found. Conclusion. Self-analysis of nonsterile preparations increased student confidence to approximately 85%. A self-analysis component included in a compounding laboratory experience is beneficial in increasing student confidence in compounding skill and nonsterile preparation quality assessment.